2013
DOI: 10.1080/13825585.2012.727976
|View full text |Cite
|
Sign up to set email alerts
|

Use of near-infrared spectroscopy as a measure of cerebrovascular health in aging adults

Abstract: Neuroimaging techniques assessing oxygenation of cerebral blood (such as near-infrared spectroscopy, NIRS) may reflect general cerebrovascular health, a factor not always considered in studies comparing younger and older adults. We examined whether baseline dorsolateral prefrontal cerebral oxygenation (measured by NIRS) was related to cardiovascular risk factors and cognitive test performance in healthy older adults. We found that cardiovascular risk factors are associated with both baseline dorsolateral prefr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…For example, an acute bout of physical activity increases cognitive performance and is accompanied by higher levels of oxygenated hemoglobin in the prefrontal areas of the human brain [6,7,8,9]. A similar relationship was noticed in cross-sectional studies, which found that more hours of weekly physical activity [10] and higher cardiorespiratory fitness levels [11,12,13] are associated with higher cerebral oxygenation levels and superior cognitive performance. However, since physical-activity-induced neurobiological mechanisms (e.g., cerebral oxygen availability), which may contribute to improved cognitive performance are not fully understood yet [14,15,16], it seems helpful to apply state-of-the-art neuroimaging methods in order to foster our understanding of the effects of physical activity on cognition [17,18].…”
Section: Introductionmentioning
confidence: 71%
“…For example, an acute bout of physical activity increases cognitive performance and is accompanied by higher levels of oxygenated hemoglobin in the prefrontal areas of the human brain [6,7,8,9]. A similar relationship was noticed in cross-sectional studies, which found that more hours of weekly physical activity [10] and higher cardiorespiratory fitness levels [11,12,13] are associated with higher cerebral oxygenation levels and superior cognitive performance. However, since physical-activity-induced neurobiological mechanisms (e.g., cerebral oxygen availability), which may contribute to improved cognitive performance are not fully understood yet [14,15,16], it seems helpful to apply state-of-the-art neuroimaging methods in order to foster our understanding of the effects of physical activity on cognition [17,18].…”
Section: Introductionmentioning
confidence: 71%
“…() discovered in a cross‐section of older women (aged 50–90 years) positive links between physical activity levels, cerebrovascular function, and cognitive performance on a battery of executive function tests (even after controlling for age). Similarly, Suhr and Chelberg () reported in a cross‐section of older men and women (aged 54–89 years) positive links between physical activity levels, prefrontal cerebral oxygenation, and memory performance. Conversely, lower CBF has been associated with impaired cognition in clinical populations with disease‐related cerebrovascular impairment, both under normal conditions (e.g., in patients with Alzheimers disease; see den Abeelen, Lagro, van Beek, & Claassen, ; Lange‐Asschenfeldt & Kojda, ) and when CBF was artificially restricted (by ∼ 40% from baseline; R. S. Marshall et al., ).…”
mentioning
confidence: 80%
“…The interpretation of prefrontal activity should take into account the potential confounding effects of underlying physiological factors. For instance, fNIRS activity has been shown to be affected by the volume of underlying gray matter (Maillet and Rajah, 2013 ) and the health of the cerebrovascular and cardiovascular systems (Suhr and Chelberg, 2013 ). These factors are often compromised in older adults, for example.…”
Section: Measuring the Balance Between Automatic And Executive Contromentioning
confidence: 99%